Russian Direct Investment as a Factor of Eurasian Integration. Issue 4 (2nd April 2016) - Kuznetsov, Aleksei
Abstract : This article is based on data from monitoring Russian direct investment in the Commonwealth of Independent States (CIS) and in other Eurasian states, which was commissioned by the Eurasian Development Bank in 2001 and carried out by the Institute of World Economy and International Relations of the Russian Academy of Sciences under the author's supervision. It presents the real extent of accumulated Russian investments in the CIS and other neighboring countries, also taking into account investments via offshore jurisdictions. It explains the motives for the investment activity of Russian transnational corporations (TNCs) and shows that full business integration has not emerged in the CIS. It pays special attention to competition in the expansion of investments between Russian firms and TNCs from the CIS and China into Ukraine and Central Asia.